Characterization of a new biodegradable edible film made from salep glucomannan - Kurt, Abdullah; Kahyaoglu, Talip (ELSEVIER SCI LTD, 2014)
The aims of this study were to report the film-forming properties of salep glucomannan (SG) and characterize its physical, barrier, mechanical, sorption and thermal properties for the first time. Galactomannan films (LBG, locust bean gum; GG, guar gum) were also prepared to compare with SG films. The steady and oscillatory theological behaviors of the film solution were evaluated. The viscosity of the SG was less dependent than that of LBG and GG on temperature. The physical properties of SG films showed good potential for food applications. The oxygen and water vapor barrier properties of SG were better than LBG and GG films. SG film was less mechanically resistant than LBG but more flexible than galactomannan films. The highest transition temperature (T-g) was determined to be -11.46 +/- 0.65 degrees C for SG film. The results showed that SG has good potential for use in producing an edible film for various food applications. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Edible films; Salep; Glucomannan; Galactomannan; Film properties; Rheology; STRUCTURAL-CHARACTERIZATION; PHYSICOCHEMICAL PROPERTIES; RHEOLOGICAL PROPERTIES; MATHEMATICAL APPROACH; PHYSICAL-PROPERTIES; KONJAC GLUCOMANNAN; STARCH; Chemistry; Polymer Science